Role of arbuscular mycorrhiza in alleviating the effect of cold on the photosynthesis of cucumber seedlings - J. MA; M. JANOUŠKOVÁ; L. YE; L.Q. BAI; R.R. DONG; Y. YAN; X.C. YU; Z.R. ZOU; Y.S. LI; C.X. HE (Photosynthetica, 2019)
Arbuscular mycorrhiza (AM) is known to enhance the rate of photosynthesis in plants, but there is little information on whether this effect is maintained at low temperature when the development of AM fungi is restrained. We therefore investigated the influence of AM on gas exchange, PSII fluorescence, and some photosynthesis-related biochemical parameters in cucumber seedlings under cold stress. Cold stress decreased, as expected, the chlorophyll content, net photosynthetic rate, and parameters related to photochemical quenching, while increasing nonphotochemical quenching and sugar contents in leaves. In contrast, AM had opposite effects on most of the determined parameters; it improved the efficiency of photosynthesis in the cucumber seedlings both at cold stress and at control ambient temperature. In addition, we recorded significant alleviation of the cold stress effect on sugar contents in leaves, which indicated that higher carbon-sink strength was an important factor maintaining higher efficiency of photosynthesis in mycorrhizal cucumber seedlings under cold stress.